The silence about oral presentation skills in distance and online education: new perspectives from an Australian university preparatory programme. (4th May 2017) - McDougall, Jenny; Holden, Helen
ABSTRACT: Oral presentation skills are considered essential workplace skills and are therefore highly valued in higher education. However, research into this aspect of adult learning is limited, especially in the context of distance and online education. This paper reports on an innovative approach used in a university preparatory program in Australia. Distance students were responsible for choosing a topic, setting and audience, and assessment was based on their self-reflections on the experience. Such an approach represents a radical departure from the usual methods used to practise and assess oral presentations. In this qualitative case study, we draw on students' responses via portfolio reflections and interviews, using principles of adult learning as a framework for thematic analysis. Findings suggest that this activity fulfilled the needs of adult learners in a number of significant ways, and for some of these students, this oral presentation was a meaningful, even transformative experience.